Simulation and modeling current technologies and applications - El Sheikh, Asim Abdel Rahman; Al Ajeeli, Abid; Abu-Taieh, Evon M. O. (IGI Pub., 2008)
"This book offers insight into the computer science aspect of simulation and modeling while integrating the business practices of SM. It includes current issues related to simulation, such as: Web-based simulation, virtual reality, augmented reality, and artificial intelligence, combining different methods, views, theories, and applications of simulations in one volume"--Provided by publisher.